New South American species of Cerambycinae, and notes on Corimbion balteum Martins (Coleoptera, Cerambycidae) - Bezark, Larry G.; Santos-Silva, Antonio; Galileo, Maria Helena M. (Zootaxa, 2016)
Three new species of Cerambycinae are described from South America: Mecometopus hauseri (Clytini), from Bolivia; Cycnoderus (Cycnoderus) metallicus (Rhopalophorini), from Venezuela; and Corimbion mutabile (Neoibidionini), from Ecuador. Mecometopus hauseri and Corimbion mutabile are included in previous keys. Corrections to the original description of Corimbion balteum Martins, 1970 are presented.